2000
DOI: 10.1212/wnl.54.3.630
|View full text |Cite
|
Sign up to set email alerts
|

Seizure outcome after temporal lobectomy for temporal lobe epilepsy

Abstract: TL provides sustained, long-term benefit in patients with medically refractory TLE. Seizure-free status at 2 years from the time of surgery is predictive of long-term remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
128
2
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(150 citation statements)
references
References 14 publications
14
128
2
6
Order By: Relevance
“…37,51,64,81,82,84,85 In the remaining one-third of patients, seizures usually recur during the first postoperative year, 37,48,97 although the percentage of patients who remain seizure free may decline with longer follow-up, with reported rates as low as 53% for patients with at least 5 years of follow-up and 41% for 10 years. 3,7,28,30,48,64,90 Recent data suggest that the histopathological abnormalities underlying surgically treated drug-resistant MTLE are the main factor predictive of seizure outcome.…”
Section: Discussionmentioning
confidence: 99%
“…37,51,64,81,82,84,85 In the remaining one-third of patients, seizures usually recur during the first postoperative year, 37,48,97 although the percentage of patients who remain seizure free may decline with longer follow-up, with reported rates as low as 53% for patients with at least 5 years of follow-up and 41% for 10 years. 3,7,28,30,48,64,90 Recent data suggest that the histopathological abnormalities underlying surgically treated drug-resistant MTLE are the main factor predictive of seizure outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pediatric patients may have a more normal neurologic development, whereas adolescents and adults may have improved psychosocial outcomes (71,73). In a recent long-term study of temporal lobectomy (mean follow-up, 14 years), patients who were seizure free for 2 years after surgery were unlikely to become refractory, and none of the patients who had seizures recurring more than 1 year after surgery became refractory, suggesting that the underlying disease process was arrested (74). A direct measure of the improvement seen with surgery was demonstrated in a study in which MR spectroscopic imaging of the ipsilateral temporal lobe normalized postoperatively in patients with TLE (75).…”
Section: Can "Progressive Epilepsy" Be Halted?mentioning
confidence: 99%
“…8) Only a few reports have examined the outcome of epilepsy surgery after more than 5 years. 6,7,10,22) In the present study, the follow-up period was 5 years or more, with a mean of about 12 years, so is one of the longest reported follow-up periods of patients undergoing epilepsy surgery. 5,6,19,25,28,34) The proportion of patients remaining seizure-free postoperatively for several years shows a progressive decline, 2,5,8,25,34) although half of the patients who suffered relapse had, at most, one seizure per year.…”
Section: Discussionmentioning
confidence: 69%
“…5,22) However, the number of studies of longterm outcome has increased dramatically, and evidence of late seizure recurrence is mounting. 25) Almost all of these studies have been of patients undergoing temporal lobe resections, 7,10,14,21,26,30,32) with few long-term follow-up studies of patients undergoing extratemporal resections. 5,28) The present study evaluated the efficacy of resective surgery in patients with lesional epilepsy identified by MR imaging for postoperative long-term seizure control extending for 5 years or more.…”
Section: Introductionmentioning
confidence: 99%